Exploration of the Semantics of Inflectional Morphemes in Student Thesis Abstracts - Arbi, Anggun Purnomo (PT. Gudang Pustaka Cendekia, 2024)
This research highlights the importance of inflectional morphemes in thesis abstracts which aim to improve clarity and meaning. This research examines the use of inflectional morphemes by alumni of the Master of English Education Program at STKIP PGRI Sidoarjo. This research uses a qualitative approach with data obtained from thesis abstracts. The findings of this study reveal that the use of plural morphemes, possessive, present tense, past tense, and present participle has a significant role in increasing semantic richness and grammatical structure. The study concludes that the understanding and proper use of inflectional morphemes can significantly improve the quality of academic writing. This study also fills a gap in the academic literature and offers practical insights for students and researchers to perfect their writing skills.